Respuesta :
Answer:
x= - 143
Step-by-step explanation:
x/11 -3 = -16
transpose the -3 first
x/11= -16+3
x/11= -13
transpose the 11
x= -13×11
x= - 143
Answer: x=-143
Why:
Since we are given the function/equation of (x/11)-3=-16, we must use reverse operations in order to solve for the value of x.
First, we must first ADD 3 to both sides in order to begin our isolation of the x variable. This cancels out the -3 on the left side and adds 3 to the right side. Since we already have -16, adding 3 will give us -13. Now we have the equation of (x/11)=-13.
And now, in order to get rid of the 11, we must do the opposite of diving (since we see the x is being divided by 11). So by MULTIPLYING by 11 on both sides, we have now canceled out the 11 on the left side and multiplied the -13 on the right side by 11. Given that -13 times 11 equals -143, this will give you the final result of x=-143.
Why:
Since we are given the function/equation of (x/11)-3=-16, we must use reverse operations in order to solve for the value of x.
First, we must first ADD 3 to both sides in order to begin our isolation of the x variable. This cancels out the -3 on the left side and adds 3 to the right side. Since we already have -16, adding 3 will give us -13. Now we have the equation of (x/11)=-13.
And now, in order to get rid of the 11, we must do the opposite of diving (since we see the x is being divided by 11). So by MULTIPLYING by 11 on both sides, we have now canceled out the 11 on the left side and multiplied the -13 on the right side by 11. Given that -13 times 11 equals -143, this will give you the final result of x=-143.